Math, asked by aditi202062, 1 year ago


 \frac{ - 2}{3}  -  \frac{5}{6}

Answers

Answered by AbhijithPrakash
8

Answer:

\dfrac{-2}{3}-\dfrac{5}{6}=-\dfrac{3}{2}\quad \left(\mathrm{Decimal:\quad }\:-1.5\right)

Step-by-step explanation:

\dfrac{-2}{3}-\dfrac{5}{6}

\gray{\mathrm{Apply\:the\:fraction\:rule}:\quad \dfrac{-a}{b}=-\dfrac{a}{b}}

=-\dfrac{2}{3}-\dfrac{5}{6}

\black{\mathrm{Least\:Common\:Multiplier\:of\:}3,\:6:\quad 6}

\black{\mathrm{Adjust\:Fractions\:based\:on\:the\:LCM}}

\gray{\mathrm{Multiply\:each\:numerator\:by\:the\:same\:amount\:needed\:to\:multiply\:its}} \gray{\mathrm{corresponding\:denominator\:to\:turn\:it\:into\:the\:LCM}\:6}

\gray{\mathrm{For}\:\dfrac{2}{3}:\:\mathrm{multiply\:the\:denominator\:and\:numerator\:by\:}\:2}

\dfrac{2}{3}=\dfrac{2\cdot \:2}{3\cdot \:2}=\dfrac{4}{6}

=-\dfrac{4}{6}-\dfrac{5}{6}

\gray{\mathrm{Since\:the\:denominators\:are\:equal,\:combine\:the\:fractions}:\quad \dfrac{a}{c}\pm \dfrac{b}{c}=\dfrac{a\pm \:b}{c}}

=\dfrac{-4-5}{6}

\gray{\mathrm{Subtract\:the\:numbers:}\:-4-5=-9}

=\dfrac{-9}{6}

\gray{\mathrm{Apply\:the\:fraction\:rule}:\quad \dfrac{-a}{b}=-\dfrac{a}{b}}

=-\dfrac{9}{6}

\gray{\mathrm{Cancel\:the\:common\:factor:}\:3}

=-\dfrac{3}{2}


BloomingBud: nice :)
Similar questions